Lateral Force between Wheel and Rail during Curve Negotiation of a Limited Express Diesel Car with Forced Steering Bogie - SATO, Eisaku; TAMAOKI, Syunji; KOBAYASHI, Hideyuki; KAKINUMA, Hirohiko; TEZUKA, Kazuhiko; OKAMOTO, Isao (Transactions of the Japan Society of Mechanical Engineers Series C, 1998)
In order to shorten travel time of a limited express train operated between Sapporo and Kusiro, the tilting diesel car called series DC 283 with a forced steering bogie had been developed by JR Hokkaido and RTRI. The regular operation of the train was started in March, 1997. This paper describes the lateral force between wheel and rail as observed on curve in field tests and that obtained from computer simulations. The influences of varying of steering ratio and wheel tread profile on the lateral forces were verified through simulations and field tests. The results of simulations and field tests are as follows; (1) The lateral force can be reduced by employing the forced steering bogie. (2) The decrease of the lateral force due to the forced steering bogie should be verified not only on circular curve but also on transition curve. (3) The lateral force of first wheelset is the largest. (4) The lateral force can also be reduced by using an arc profile tread on trasition curve. (5) In circuler curve, the steering performance is less dependent on wheel profile.